Transcriptome Analysis of Differentially Expressed Genes Involved in Proanthocyanidin Accumulation in the Rhizomes of Fagopyrum dibotrys and an Irradiation-Induced Mutant - Chen, Caixia; Li, Ailian (Frontiers in Physiology, 2016)
The rhizome of Fagopyrum dibotrys is a traditional Chinese medicine that has recently gained attention due to substantial findings regarding its bioactive proanthocyanidin (PA) compounds. However, the molecular mechanism underlying PA accumulation in F.dibotrys remains elusive. We previously obtained an irradiation-induced mutant (RM_R) of F.dibotrys that had a higher PA content compared to that of the wild-type (CK_R). The present study aimed to elucidate the molecular mechanism underlying PA accumulation in F. dibotrys by comparing the rhizome transcriptomes of the irradiation-induced mutant and wild-type using RNA-seq analysis. A total of 53,540 unigenes were obtained, of which 29,901 (55.84%) were annotated based on BLAST searches against public databases, and 501 unique sequences were differentially expressed between the two samples, which consisted of 204 upregulated and 297 down regulated unigenes. Further analysis showed that the expression patterns of some unigenes encoding enzymes involved in PAs biosynthesis in F.dibotrys rhizomes differed between RM_R and CK_R. In addition, we identified transcription factor families and several cytochrome P450s that may be involved in PA regulation in F. dibotrys. Finally, 12 unigenes that encode PA biosynthetic enzymes were confirmed by qRT-PCR analysis. This study sheds light on the molecular mechanism underlying radiation-mediated flavonoid accumulation and regulation in F. dibotrys rhizomes. These results will also provide a platform for further functional genomic research on this particular species.